2014
DOI: 10.1002/cam4.231
|View full text |Cite
|
Sign up to set email alerts
|

Decreased decorin expression in the tumor microenvironment

Abstract: Decorin is a small leucine-rich proteoglycan, synthesized and deposited by fibroblasts in the stroma where it binds to collagen I. It sequesters several growth factors and antagonizes numerous members of the receptor tyrosine kinase family. In experimental murine systems, it acted as a potent tumor suppressor. Examining the Human Protein Atlas online database of immunostained tissue samples we have surveyed decorin expression in silico in several different tumor types, comparing them with corresponding normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…The first link between DCN and cancer was established by Iozzo et al who showed that DCN/p53 double knockout mice developed tumors faster than their wild‐type counterparts . The tumorigenic role of DCN has subsequently been studied in various experimental models . In addition, DCN expression is markedly reduced in tumor tissues, including those of lung cancer, hepatocellular carcinoma, CRC and ovarian cancer, indicating a tumor suppressive function of DCN.…”
Section: Introductionmentioning
confidence: 99%
“…The first link between DCN and cancer was established by Iozzo et al who showed that DCN/p53 double knockout mice developed tumors faster than their wild‐type counterparts . The tumorigenic role of DCN has subsequently been studied in various experimental models . In addition, DCN expression is markedly reduced in tumor tissues, including those of lung cancer, hepatocellular carcinoma, CRC and ovarian cancer, indicating a tumor suppressive function of DCN.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction of decorin expression is seen in the microenvironments of low- and high-grade urothelial carcinoma [59] as well as in the plasma of multiple myeloma and MGUS patients [60], cases of esophageal squamous cell carcinoma [61] and instances of colon cancer [53]. An in silico -based query utilizing immunohistochemical arrays spanning a variety of tissues has detected a marked reduction of decorin expression in the stroma of many solid malignancies, including breast [62]. Other studies seemingly report the opposite result inasmuch as certain tumor types, including colon and breast carcinomas [54], have elevated amounts of stromally-deposited decorin.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have since shown that DCN can bind to a wide variety of growth factors and receptors, therefore, regulating various cellular processes such as proliferation and cell migration (Neill et al, 2012). Dcn is generally characterized as anti-proliferative and has been identified as a tumor suppressor in various organs and tissues, including the prostate (Suhovskih et al, 2013, Bozoky et al, 2014. Dcn is generally characterized as anti-proliferative and has been identified as a tumor suppressor in various organs and tissues, including the prostate (Suhovskih et al, 2013, Bozoky et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the role of the collagen matrix in guiding ductal growth and branching in the developing mammary gland (Nelson and Bissell, 2006;Schedin and Keely, 2011). DCN, a small leucine rich proteoglycan, is a component of the ECM that binds to and organizes collagen fibrillogenesis and has been previously identified as a tumor suppressor in prostate cancer Suhovskih et al, 2013;Bozoky et al, 2014;Xu et al, 2015). DCN, a small leucine rich proteoglycan, is a component of the ECM that binds to and organizes collagen fibrillogenesis and has been previously identified as a tumor suppressor in prostate cancer Suhovskih et al, 2013;Bozoky et al, 2014;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%